PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN MEREK, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN J&T EXPRESS (Studi Pada Masyarakat Kecamatan Cinere) - Tiyarra Syanjari (2023)
This study is a quantitative study aimed at identifying, proving and analyzing the impact of service quality, brand trust, and brand image on J&T Express customer satisfaction. The population used in this study is either on or off the J&T Express expedition. The sample used in this study used 100 community respondents in Cinere District. The sampling method uses Non-probability sampling with purposive sampling techniques and is analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. Thus, data processing has the result that (1) Quality of Service has a positive and significant effect on Customer Satisfaction, (2) Brand Trust has a positive and significant effect on Customer Satisfaction, (3) Brand Image has no effect on Customer Satisfaction.